Systematic identification of cancer-associated-fibroblast-derived genes in patients with colorectal cancer based on single-cell sequencing and transcriptomics - Zhao, Jia; Chen, Ying (Frontiers in Immunology, 2022)
Colorectal cancer (CRC) has a high incidence rate and poor prognosis, and the available treatment approaches have limited therapeutic benefits. Therefore, understanding the underlying mechanisms of occurrence and development is particularly crucial. Increasing attention has been paid to the pathophysiological role of cancer-associated fibroblasts (CAFs) in the heterogeneous tumour microenvironment. CAFs play a crucial role in tumorigenesis, tumour progression and treatment response. However, routine tissue sequencing cannot adequately reflect the heterogeneity of tumours. In this study, single-cell sequencing was used to examine the fibroblast population in CRC. After cluster analysis, the fibroblast population was divided into four subgroups. The distribution and role of these four subgroups in CRC were found to be different. Based on differential gene expression and lasso regression analysis of the main marker genes in these subgroups, four representative genes were obtained, namely, TCF7L1, FLNA, GPX3 and MMP11. Patients with CRC were divided into the low- and high-risk groups using the prognostic risk model established based on the expression of these four genes. The prognosis of patients in different risk groups varied significantly; patients with low-risk scores had a greater response to PDL1 inhibitors, significant clinical benefits and significantly prolonged overall survival. These effects may be attributed to inhibition of the function of T cells in the immune microenvironment and promotion of the function of tumour-associated macrophages.